QLIKVIEW APPLICATION - SUPPORT IN DECISION MAKING - Luminita SERBANESCU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
Control over the company, an objective that any manager wants, can only be exercised on the basis of real and complex business data. For this, a higher level of application is required, with Business Intelligence applications that provide information that no one else can offer faster. Winning time can be used to identify other issues related to available information or activities that add value to the company. After all, management time is a decision, and the decision is valuable only if it occurs at the right time. In this article I presented the benefits of implementing a business intelligence solution in a company, as well as how to design analytical reports using the QlikView application.